Pemberian Gamal Tambahan dalam Ransum Meningkatkan Neraca Nitrogen dan Populasi Mikrob Proteolitik Rumen Sapi Bali (ENHANCEMENT PROVISION OF GLIRICIDIA SEPIUM IN DIET INCREASE NITROGEN BALANCE AND POPULATION OF RUMEN PROTEOLITIK MICROORGANISM OF BALI CATT - Suryani, Ni Nyoman; Mahardika, I Gede; Putra, Sentana; Sujaya, Nengah (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
This research aimed to study the effect of different forage composition in diet on nitrogen balance andmicrobial population of Bali cattle. Randomized Block Design consisted of four feed treatments with 3block of weight live as replicates were used in this study. Body weight of male bali cattle used rangedbetween 181-265 kg. These four treatments based on dry matter were: A (45% elephant grass + 0% ricestraw + 15% glyricidia + 10% calliandra + 30% concentrate); B (30% elephant grass +10% rice straw + 20%glyricidia + 10% calliandra+ 30% concentrate) ; C (15% elephant grass +20% rice straw + 25% glyricidia+10% calliandra + 30% concentrate) and D (0%elephant grass + 30% rice straw + 30% glyricidia + 10%calliandra+ 30% concentrate) . Variables measured were nitrogen balance and rumen microbial population.The collected data were analyzed by analysis of variance. The result showed that nitrogen intake in cattlefed with diet C was significantly (P<0.05) higher than these in other treatments and nitrogen retention(P<0.05) was significantly higher as compared to those fed with diet A. Amylolytic and cellulolytic bacterialpopulations were not significantly different (P>0.05) among all treatments, but the population of proteolyticbacteria was found the lowest (P<0.05) in cattle fed with diet A. It can be concluded that increasedglyricidia and rice straw in the diet could increased nitrogen intake, nitrogen retention and proteolyticbacterial population.
Keywords: nitrogen balance, rumen microbial population, Bali cattle